2021
DOI: 10.1057/s41287-021-00484-z
|View full text |Cite|
|
Sign up to set email alerts
|

The Dynamics and Role of Gender in High-Value Avocado Farming in Kenya

Abstract: We used two-wave panel data obtained from avocado growers in Murang'a County in Kenya to examine, through the perspective of gender, the dynamics of farmers' participation in avocado production and marketing organizations (PMOs), and test whether understanding group dynamics is important for analyzing contract farming. Using a multinomial logit (MNL) model, we identify the characteristics of men and women participating in PMOs categorized as early adopters, dis-adopters, late adopters, and non-adopters. We foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…They also revealed that group and contracting dynamics were related and recommended policy efforts to focus on supporting women farmers to enhance their participation in avocado production and marketing organisations (PMOs) PMOs, which ultimately affects contracting. Muriithi & Kabubo-Mariara (2022) also underscore the need to improve access to high-yielding avocado varieties and build capacity in orchard management that would enhance women's decision-making including group participation, contracting, and marketing. In addition, they recommend the provision of low-cost agricultural credit that would also improve women's ownership of improved avocado trees and hence their participation in high-value markets.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…They also revealed that group and contracting dynamics were related and recommended policy efforts to focus on supporting women farmers to enhance their participation in avocado production and marketing organisations (PMOs) PMOs, which ultimately affects contracting. Muriithi & Kabubo-Mariara (2022) also underscore the need to improve access to high-yielding avocado varieties and build capacity in orchard management that would enhance women's decision-making including group participation, contracting, and marketing. In addition, they recommend the provision of low-cost agricultural credit that would also improve women's ownership of improved avocado trees and hence their participation in high-value markets.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Multinomial logit is used in cases where the dependent variable has many choices [8]. Other models used are the negative binomial regression, logistic regression, and Poisson [17]. These models use cross-sectional data and are not suitable for the current study, which uses panel data.…”
Section: Theoretical Framework and Empirical Approachmentioning
confidence: 99%
“…The variable was specified as a dummy variable; a farmer using MAT was assigned one and zero otherwise for the adoption model, while one who used the technology before and stopped was assigned one and zero otherwise in the dis-adoption model (Table 1). The choice for independent variables included in the adoption and dis-adoption models was informed by the literature on agricultural technology adoption and, particularly, the adoption of fruit fly IPM and, in the context of our study [8,[10][11][12][13][14][15]17], includes demographic characteristics, household resources, access to information, social capital, and networking and technology attributes.…”
Section: Definition and Measurement Of Variablesmentioning
confidence: 99%
See 2 more Smart Citations